Yet two more firsts for Mary E. Barber (1818–1899), and a new synonym for the largest aloe, Aloidendron barberae (Asphodelaceae subfam. Alooideae) - Figueiredo, Estrela; Smith, Gideon F. (Phytotaxa, 2020)
Walker et al. (2019: 12) suggested that the name Aloe zeyheri (Barber 1870a: 80) (Asphodelaceae subfam. Alooideae) was merely proposed and not validly published for the species of tree aloe today known as Aloidendron barberae (Dyer 1874a: 566) Klopper & Gideon F. Sm. in Grace et al. (2013: 9) (Fig. 1A–C). Aloidendron barberae occurs naturally along the eastern seaboard of South Africa, and slightly inland, and caused quite a stir in botanical circles when it was first and more or less simultaneously collected in South Africa’s Eastern Cape and KwaZulu-Natal provinces.